2001
DOI: 10.1097/00004694-200101000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Foot Bimalleolar Angle in the Management of Congenital Talipes Equinovarus

Abstract: The study was undertaken to establish the normal foot bimalleolar (FBM) angle in Indian infants and to correlate it with the severity of deformity and results of treatment in congenital talipes equinovarus (CTEV). Foot tracings with the level of both the malleoli of 182 feet (91 normal Indian infants) were taken. The anteromedial angle between the long axis of foot and the bimalleolar plane was taken as the FBM angle. The FBM angle in normal infants was calculated as 82.5 degrees. Eighty-four CTEV (51 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 23 publications
0
15
1
Order By: Relevance
“…As far as analysis of FBA parameter is concerned, Jain et al [23] showed improvement from grade III to grade I in 93% of cases managed by Ponseti manipulation in early cases, while in present study we were able to bring FBA grade III to FBA grade I in 87.1% of our cases.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…As far as analysis of FBA parameter is concerned, Jain et al [23] showed improvement from grade III to grade I in 93% of cases managed by Ponseti manipulation in early cases, while in present study we were able to bring FBA grade III to FBA grade I in 87.1% of our cases.…”
Section: Discussioncontrasting
confidence: 43%
“…As described in the literature, the normal value of FBA is 82.5°. Feet were classified in groups I, II, III as per the Jain et al study [23] (group I: >73.2°, group II: >  66.6–73.2° and group III: <66.6°). FBA was recorded before and after the treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Jain et al [16] have used the FBM angle as an evaluation method and 82.51 was mean FBM found in normal Indian infants. Grade I, grade II, and grade III severity of club feet had mean FBM angles of 73.21, 66.61, and 54.71, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The improvement in the shape of the heel and forefoot is a measure of the correction of the calcaneal rotation [16]. In FBM, an attempt is made to use the foot print to quantify the CTEV deformity depending on the objective assessment of calcaneal rotation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation